(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
We are living in a busy age. Leisure has decreased among people in the dynamic era. Many people hardly have the time and patience to enjoy reading long novels and stories. So in this era, Audio stories have become a popular means of enjoying tales. These stories are easy to listen to when the listener is busy during the work time. Different sound effects, professional storyteller, background music and various foley sounds make the stories more fascinating. Millions of people are enjoying stories through YouTube, Spotify, Storytel, Gaana and other broadcasting mediums. So in today’s era Audio stories are bound to be discussed. This is the main reason for the current discussion. In the world of Bengali audio story, the name of Satyajit Ray is bright for a special reason. The journey of Radio Mirchi’s Sunday Suspense began with the adaptation of a story written by Satyajit Ray. The first story aired with Satyajit Ray’s story ’Septopaser Khide’, on 28 June 2009. The plan was to continue this program with the story of Satyajit Ray; But keeping in mind the huge popularity and demand, the stories of other popular writers have also been converted into audio stories and are still being done today. Stories by foreign writers are also being translated and served. Nowadays, the world of Bangla audio stories has become more diverse and popular. Along with popular stories and novels, classic stories and novels are also being converted into audio stories these days. So audio stories have become an important medium in the popularity of Bengali literature. It is for this reason that the present discussion is taken up as the subject.